Stalcup, Ed., Women's Suffrage - Armstrong, Thomas (Teaching History: A Journal of Methods, 2001)
In selecting women's suffrage as a "turning point in world history," Greenhaven Press has, itself, made an important statement. The enfranchisement of more than fifty percent of the American electorate has helped transform women's lives and American politics. This collection of essays underscores the significant trends that made up the movement. The collection is also arranged in a format convenient for use in college classrooms.